ЦЕРУЛОПЛАЗМИН В АДАПТАЦИИ ОРГАНИЗМА К ГИПОКСИИ (Eurasian Journal of Ecology, 2016)
It had been study the effect of ceruloplasmin and malonic aldehyd on the adaptation to interrupt hypobaric hypoxia. Individual character of the organism adaptive reaction to hypoxia had been ascertain.